A PEAR1 polymorphism (rs12041331) is associated with risk of coronary artery aneurysm in Kawasaki disease. (7th September 2018) - Pi, Lei; Xu, Yufen; Fu, Lanyan; Zhang, Li; Liu, Yunfeng; Zhou, Huazhong; Che, Di; Gu, Xiaoqiong
Abstract: Kawasaki disease (KD) is an acute systemic vasculitis that is most seriously complicated by coronary artery aneurysm (CAA). The polymorphisms of platelet endothelial aggregation receptor 1 ( PEAR1 ), notably rs12041331 and rs12566888, were found to be closely related to cardiac disease. However, little is known regarding the connection between PEAR1 and KD. In this study, we genotyped PEAR1 rs12566888 and rs12041331 in 637 healthy infants and 694 KD patients (74 with CAA). Subsequently, odds ratio (OR) and 95% confidence interval (CI) were calculated to assess the strength of their relationships. No significant differences in the frequency of rs12566888 or rs12041331 in PEAR1 were observed between KD and healthy controls. However, regardless of the statistical combination of rs12566888 genotype, the rs12041331 recessive inheritance model was associated with an increased risk of CAA after Bonferroni correction (for rs12041331, AA vs. GG/GA: adjusted OR = 2.37, 95% CI = 1.41–4.01, P  = 0.009; combination of two recessive genotypes vs. combination of 0–1 recessive genotypes: adjusted OR = 2.39, 95% CI = 1.42–4.04, P  = 0.009). This study suggests for the first time that PEAR1 polymorphisms did not indicate susceptibility for KD occurrence but the rs12041331 polymorphism was associated with increased risk of CAA formation in KD, and the functions of the gene warrant further research.